Prognostic and predictive values of tumour budding in stage IV colorectal cancer - Nagata, K. (BJS Open, 2020)
BACKGROUND: Tumour budding is an important prognostic feature in early‐stage colorectal cancer, but its prognostic significance in metastatic disease has not been fully investigated. METHODS: Patients with stage IV disease who had primary colorectal tumour resection without previous chemotherapy or radiotherapy from January 2000 to December 2018 were reviewed retrospectively. Budding was evaluated at the primary site and graded according to the criteria of the International Tumor Budding Consensus Conference (ITBCC) (BD1, low; BD2, intermediate; BD3, high). Patients were categorized by metastatic (M1a, M1b) and resectional (R0/R1, R2/unresected) status. Subgroups were compared for overall (OS) and recurrence‐free (RFS) survival in R0/R1 subgroups; R2/unresected patients were evaluated for the rate of tumour progression, based on change in tumour size from baseline. RESULTS: Of 371 patients observed during the study, 362 were analysed. Patients with BD3 had a lower 5‐year OS rate than those with BD1 + BD2 (18·4 versus 40·5 per cent; P < 0·001). Survival analyses according to metastatic and resection status also showed that BD3 was associated with shorter OS than BD1 + BD2. In multivariable analysis, BD3 (hazard ratio (HR) 1·51, 95 per cent c.i. 1·11 to 2·10; P = 0·009), T4 status (HR 1·39) and R2/unresected status (HR 3·50) were associated with decreased OS. In the R0/R1 subgroup, the 2‐year RFS rate was similar for BD3 and BD1 + BD2 according to metastatic status. There was no significant difference between BD3 and BD1 + BD2 for change in tumour size in the R2/unresected subgroup (P = 0·094). Of 141 patients with initially unresectable metastases who had chemotherapy, 35 achieved conversion from unresectable to resectable status. The conversion rate was significantly higher for BD1 + BD2 than for BD3 (36 versus 18 per cent; P = 0·016). CONCLUSION: Stage IV colorectal cancer with high‐grade tumour budding according to ITBCC criteria correlates with poor prognosis.